Urgensi Kegiatan Islami terhadap Perkembangan Sosial Emosional Anak Usia Dini - Mutaqin, Mumu Zainal; Bahri, Saepul; Sanusi, Sanusi; Inayatullah, Deden; Husnun, Nunu (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2025)
This study aims to examine in depth the urgency of Islamic activities for the social and emotional development of early childhood. This study uses a qualitative approach with a literature study type. Literature studies were chosen to explore and analyze various scientific literature, books, and other relevant sources that discuss Islamic activities, instilling Islamic values, social and emotional development of early childhood, and the relationship between the two. The results of this literature study indicate that Islamic activities have a significant role in instilling Islamic values ​​such as honesty, compassion, cooperation, and respect for others in early childhood. Instilling these values ​​is an important foundation in forming positive social behavior and the ability to build healthy relationships. Furthermore, this study also identified that Islamic activities contribute to children's emotional development through the introduction of calming religious concepts, learning about emotional management, and fostering empathy and caring. Islamic activities not only provide religious knowledge, but also actively stimulate children's social development through positive interactions, understanding social norms, and developing empathy. In addition, Islamic activities also play an important role in shaping children's emotional maturity through recognizing emotions, developing self-regulation skills, and fostering resilience. Thus, this study concludes that Islamic activities are a crucial element in supporting the holistic social and emotional development of early childhood.